Financial Self-Efficacy and General Life Satisfaction: The Sequential Mediating Role of High Standards Tendency and Investment Satisfaction - Hu, Jianping; Quan, Lei; Wu, Yanwei; Zhu, Jia; Deng, Mingliang; Tang, Song; Zhang, Wei (Frontiers in Psychology, 2021)
Important strides have been made toward understanding the relationship between self-efficacy and life satisfaction. However, existing studies have largely focused on work and academic domains, leaving self-efficacy in the finance domain less frequently investigated. The present study applied the self-efficacy construct to the finance domain, namely “financial self-efficacy” (FSE), and tested the sequential mediating roles of high standards tendency and investment satisfaction in the relationship between FSE and general life satisfaction. A total of 323 employees from finance-related businesses completed anonymous questionnaires regarding FSE, high standards tendency, investment satisfaction, and general life satisfaction. Results indicated that FSE influenced general life satisfaction through investment satisfaction, and sequentially through high standards tendency and investment satisfaction. These results provide contributions to the current literature on life satisfaction, and positive psychology literature by shedding light on the roles of high standards tendency and investment satisfaction in the relation between FSE and general life satisfaction.